Analisis Biaya Perawatan Pasien Stroke di Rumah Sakit Royal Prima Tahun 2020 - Panta Leon Raynard Aditia Kaban; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the cost of illness stroke in patients treated at RSU Royal Prima Medan—this partial economic evaluation research with a retrospective approach using secondary data. The results of this study indicate that the direct medical cost of a stroke at RSU Royal Prima Medan reached IDR 2,403,132,163, and the direct non-medical price reached IDR 809,484,699, with a range of charges billed to patients between IDR 3,832,436 to IDR 142,986,392 and duration of hospitalization between 1 and 25 days of hospitalization. In conclusion, the average cost of illness for stroke at RSU Royal Prima Medan reached Rp. 20,861,148 ± Rp. 22,880,177 per episode per patient with an average stay of 6.45 ± 3.40 days. Keywords: Cost of Illness, Direct Cost, Hospitalization, Stroke